A Socio-technical Approach to Evaluating an Electronic Medical Record System implemented in the Public Health Services of Aguascalientes - Díaz de León Castañeda, Christian (Revista Mexicana de Ingenieria Biomedica, 2020)
The objective of this study was to explore a strategy for evaluating an Electronic Medical Record (EMR) system implemented in the public health services of Aguascalientes, Mexico. A questionnaire based on DeLone and McLean’s Model of Information Systems Success (MISS) was adapted to Spanish and applied with 62 primary care physicians working in health centers of the Instituto de Servicios de Salud del Estado de Aguascalientes (ISSEA or the State of Aguascalientes Institute for Health Services). Opportunities for improving EMR systems were also explored from the informants’ perspectives. Additionally, the relationships between MISS components were analyzed using Structural Equations Modeling (SEM). Some MISS components and particular items (service quality and overall satisfaction) presented low averages, reflecting opportunities for improving the development and implementation of EMR, such as the need to continuously update information pertaining to diagnostic and medicine catalogs and develop systems that are interoperable between the second and third levels of care. In conclusion, the present study contributes generating evidence on the use of the MISS to evaluating EMR systems in public health services of Mexico. More evidence should be generated in this field in order to promote the continuous improvement of these information systems.